A cena constituinte da psicose maníaco-depressiva no Brasil The emergence of manic depressive psychosis as a diagnosis in Brazil - Joel Birman (História, Ciências, Saúde: Manguinhos, 2010)
A intenção deste ensaio é esboçar a leitura da psicose maníaco-depressiva no Brasil, no começo do século XX. Destaca a transformação teórica ocorrida na psiquiatria brasileira, que se deslocou da tradição francesa para a alemã. Sublinha o modo como a problemática da histeria foi substituída pela da psicose maníaco-depressiva nesse contexto histórico. This essay examines the early twentieth-century interpretation of manic depressive psychosis in Brazil, during a moment when Brazilian psychiatry witnessed a theoretical shift from the French to German traditions. It calls special attention to how the problem of hysteria was replaced by manic depressive psychosis within this historical context.